INNOVATION IN KATUK LEAF-BASED PRODUCTS ROOTED IN COASTAL LOCAL WISDOM TO SUPPORT BREAST MILK PRODUCTION AND HEALTH SELF-SUFFICIENCY AMONG BREASTFEEDING MOTHERS - Mien Mien; Hasrima Hasrima; Risnawati Risnawati; Nanda Nanda; Adeliya Adeliya (LPPM Universitas Flores, 2026)
Exclusive breastfeeding is recognized as one of the most effective interventions for improving maternal and infant health. However, breastfeeding practices remain influenced by mothers' limited knowledge and the underutilization of local food resources that may support milk production. Katuk leaves (Sauropus androgynus) are traditionally known as a natural galactagogue, although their use in coastal communities is still largely confined to vegetable dishes. This community service program aims to strengthen the knowledge and practical skills of breastfeeding mothers through health education and training on the preparation of katuk leaf nuggets as a local functional food. The program was implemented in the working area of Puskesmas Mata, Kendari City, involving 25 breastfeeding mothers. Activities consisted of health education, demonstrations, practical sessions, mentoring, and evaluation using a 10-item knowledge questionnaire and a 12-item observational checklist. Changes in participants' scores before and after the intervention were analyzed using the Wilcoxon Signed-Rank Test. The findings indicated a significant improvement in knowledge, with the median score increasing from 6 to 8 (p < 0.05). Practical skills also improved significantly, with the median score increasing from 6 to 11 (p < 0.05). Before the training, all participants were categorized as unskilled, whereas 96% achieved the skilled category after the intervention. To encourage sustainability, participants received educational modules, recipe booklets, leaflets, product samples, and packaging labels. The program demonstrated that combining health education with practical training based on locally available resources can strengthen community capacity to support exclusive breastfeeding and may be adopted as part of routine maternal and child health promotion activities.